Ukuran Risiko dan Hedging Dengan dan Tanpa Derivatif pada Perusahaan Pertambangan - Liong, Kek (Jurnal Studi Pemerintahan dan Akuntabilitas, 2024)
Purpose: The general aim of this research is to identify gold price risk and USD exchange rate risk on equity returns and identify gold price risk and USD exchange rate risk on asset returns. Method: This research refers to previous research conducted by Mitchell A. Petersen and S. Ramu Thiagarajan (Financial Management, Winter 2000). The method used in this research is the correlational method because it looks at the relationship between the return side and the risk side, while the data analysis method uses a relational test or parametric test in the form of a t-test. Result: Analysis of gold price risk and USD exchange rate risk on the ROE. Statistical testing for existing hypotheses using the multiple linear regression method simultaneously to determine the level of influence between gold price risk, USD exchange rate risk, and ROE in PT Aneka Tambang Tbk (ANTAM) and PT Newmont Indonesia using the SPSS program. Limitations: The methodology is limited to the exploratory research aspect, and variables are limited to using a ratio scale, factors, and circumstances not covered: Political, Social and Cultural. Contribution: Benefits of research: It is hoped that the results of this study can provide valuable thought and input for Risk Management to create value for shareholders. Risk Management can increase company value, knowledge and experience of researchers, previous research, government income, and professionals.